Pharmacoeconomic assessment of type 2 diabetes mellitus care on the base of Endocrinology Research Centre, Moscow - Ivan Ivanovich Dedov (Endocrinology Research Centre, 2012)
Aims. To assess the development of medical care and pharmacological treatment at Endocrine Research Centre (ERC), Moscow, forthe period of 2010-2011 years.Materials and Methods. We analyzed files of 100 patients with type 2 diabetes mellitus (T2DM), who underwent hospitalization to ERCafter January 1, 2010. Key parameters were assessed by means of a study chart, applied for every patient file. Mean values, medians,fractions and confidence intervals (CI) were calculated for studied parameters. Various methods of parametric and non-parametricstatistics were used for comparison of acquired values. Results. Files of 100 patients with T2DM, hospitalized to Endocrinology Research Centre, were analyzed to obtain clinical characteristicsand evaluate initial (prior to hospitalization) and optimized (after hospitalization) therapeutic schemes, as well as spendingpatterns. Mean patient age exceeded 63 years, mean duration period of T2DM was greater than 14.4 years. 86% of patients weredecompensated for glycemic metabolism. 8% were diagnosed with less than 3 diabetes complications, 66% were found to have from 3to 6 complications. Almost all studied cases (98%) featured elevated blood pressure, 63% - diabetic retinopathy on different stages,59% - IHD, 51% - cataract, 49% - CKD. Lower limb angiopathy was found in 30% of cases, diabetic foot syndrome - in 15%.2 patients lost their vision due to diabetic complications and 3 patients experienced lower limb amputation. Arterial hypertension wascompensated in 14 cases from total of 98.Correction of therapy decreased fraction of patients on oral hypoglycemic agents and intermediate acting insulin (NPH), while prescriptionfrequency of short acting insulin and rapid acting human insulin analogues (as well as long acting analogues) showed oppositetrend. Optimization of therapy also included prescription of hypolipidemic drugs for majority of patients, as well as various agents forcorrection of coagulation abnormalities, treatment for CVD and other complications of T2DM.Due to described measures cost of per day treatment for 100 patients increased 2.28 times: from 8 982 RUB to 20 440 RUB (averagecost per day increased from 89.8 RUB to 204.1 RUB).Following the correction, fraction of patients with fasting glycemia 9.0 mmol/l dropped from 37% to 9%, and that with postprandial glycemia >10.0 mmol/l - from 27% to 1%.Mean fasting glycemia level decreased from 8.6 mmol/l to 6.8 mmol/l.Conducted analysis shows that prime expenditures (more that 36% from total cost structure) were associated with hospital stay (includingintensive care unit). Conclusion. Considering expanding nature of DM epidemic, there is an urgent need for effective healthcare management and preventionof severe cardiovascular complications. Priority should be established on balancing efficiency of hypoglycemic agents with theirsafety for short- and long-term prognosis.